2013
DOI: 10.2298/abs1303069p
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature, relative humidity and light on conidial germination of oak powdery mildew (Microsphaera alphitoides Griff. et Maubl.) under controlled conditions

Abstract: The influence of temperature, humidity and light on the conidial germination and germ tube elongation of oak powdery mildew (Microsphaera alphitoides Griff. et Maubl.) was studied in controlled conditions. The maximal germ tube length was attained at 25°C, whereas at lower and higher than optimal temperatures, germ tube growth was significantly lower. Germ tubes begin to develop at all values of relative humidity (10-100%), reaching the maximum length at 90%. The development of germ tubes was the most in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Mild temperatures favoured the development of E. cruciferarum . The finding in the current study that the maximum growth of E. cruciferarum germ tubes was reached at 15–20 °C and survival of conidia was reduced by temperatures greater than 30 °C is similar to results published for other genera and/or species of powdery mildew such as E. necator (Moyer et al ., ; Peduto et al ., ), P. macularis (Peetz et al ., ), Microsphaera alphitoide s (Pap et al ., ) and Podosphaera clandestina (Grove, ). Ambient temperature is one of the factors that dramatically affects the success of powdery mildew infections, and mild temperatures generally favour the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Mild temperatures favoured the development of E. cruciferarum . The finding in the current study that the maximum growth of E. cruciferarum germ tubes was reached at 15–20 °C and survival of conidia was reduced by temperatures greater than 30 °C is similar to results published for other genera and/or species of powdery mildew such as E. necator (Moyer et al ., ; Peduto et al ., ), P. macularis (Peetz et al ., ), Microsphaera alphitoide s (Pap et al ., ) and Podosphaera clandestina (Grove, ). Ambient temperature is one of the factors that dramatically affects the success of powdery mildew infections, and mild temperatures generally favour the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in latent period and spore volume might have been affected by an unidentified environmental factor. Even though inoculated leaf disks were incubated under controlled conditions of temperature and light, micro-scale variation may have occurred for these crucial parameters influencing fungal development and infection dynamics ( Cochrane, 1959 ; Rotem et al, 1978 ; Trapero-Casas and Kaiser, 1992 ; Turechek and Stevenson, 1998 ; Turechek et al, 2001 ; Pap et al, 2013 ). Moreover, the initial position of the disk in the leaf might have influenced infection outcome ( Katsuya and Green, 1967 ; Johnston et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to providing shorter leaf wetness, temperature changes provided by the trees in ASP may have contributed directly to greater PM severity. It was demonstrated that low variation in temperature favors M. diffusa (Phillips 1984;Alves et al 2009;Pap et al 2013), while greater variation reduces infection. In the present work, a smaller temperature difference was observed in the ASP, with similar nighttime and daytime temperatures.…”
Section: Discussionmentioning
confidence: 99%